RUANG KONFIGURASI SUATU SISTEM - Rahmawati Pane (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2008)
A system in addition to having properties - properties also have any configuration needed - time operation system or process. A configuration based on the properties - properties that will be raised and the purposes of the system. This paper proposes a system configuration based on the uniformity properties of woven and aid group obtained a mathematical model rather than the system.